Hubungan Penggunaan Sosial Media dengan Kecerdasan Moral Mahasiswa Tingkat Pertama Fakultas Keperawatan Universitas Jember - Indra Stiawan; Erti Ikhtiarini Dewi; Enggal Hadi Kurniawan (Pustaka Kesehatan, 2021)
The behavior of adolescents who use social media excessively unwisely affects juvenile delinquency, which can reduce adolescent moral intelligence. The study aimed to analyze the relationship between the use of social media and moral intelligence. This study used an observational study with a cross-sectional approach. The population of first-level students of the Faculty of Nursing at the University of Jember was 190, which was then calculated using a purposive sampling technique and 128 respondents. BSMAS and MCI questionnaire used a Likert scale with a reliability value of a = 0.875 found 18 valid items and = 0.985, obtained 40 valid items. The data analysis used was Kendall's Tau b test. The correlation between the use of social media and moral intelligence (p = 0.000; a<0.05), the lower the use of social media in adolescents, indicates that adolescents have high moral intelligence.